2015
DOI: 10.1126/science.aaa1958
|View full text |Cite
|
Sign up to set email alerts
|

Experimental nutrient additions accelerate terrestrial carbon loss from stream ecosystems

Abstract: Nutrient pollution of freshwater ecosystems results in predictable increases in carbon (C) sequestration by algae. Tests of nutrient enrichment on the fates of terrestrial organic C, which supports riverine food webs and is a source of CO2, are lacking. Using whole-stream nitrogen (N) and phosphorus (P) additions spanning the equivalent of 27 years, we found that average terrestrial organic C residence time was reduced by ~50% as compared to reference conditions as a result of nutrient pollution. Annual inputs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
214
2
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(231 citation statements)
references
References 43 publications
10
214
2
5
Order By: Relevance
“…This general pattern appears to hold across a wide range of terrestrial and aquatic ecosystems, suggesting that large inputs of nitrogen or carbon to floodplain systems could change substrate stoichiometry and impact ecosystem respiration and nitrogen retention and removal. For instance, Rosemond et al (2015) found that average residence time of terrestrially-derived particulate organic carbon decreased by half under high nitrogen availability during a long-term experiment manipulating loworder streams with various nitrogen applications. Under anoxic conditions, however, stoichiometric constraints of carbon and nitrogen supply are often secondary to redox conditions in controlling overall nitrogen uptake and loss (Helton et al, 2015).…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 99%
“…This general pattern appears to hold across a wide range of terrestrial and aquatic ecosystems, suggesting that large inputs of nitrogen or carbon to floodplain systems could change substrate stoichiometry and impact ecosystem respiration and nitrogen retention and removal. For instance, Rosemond et al (2015) found that average residence time of terrestrially-derived particulate organic carbon decreased by half under high nitrogen availability during a long-term experiment manipulating loworder streams with various nitrogen applications. Under anoxic conditions, however, stoichiometric constraints of carbon and nitrogen supply are often secondary to redox conditions in controlling overall nitrogen uptake and loss (Helton et al, 2015).…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 99%
“…Terrestrial inputs as well as autochthonous primary production of OM are the result of the interplay of several catchment attributes such as soil properties (Autio et al 2016;Nelson et al 1992), land cover (Giling et al 2014;Wilson and Xenopoulos 2009), hydrology and water residence time (Lambert et al 2014;Sanderman et al 2009) and nutrient availability (Reche et al 1998), all of these basic drivers being altered by human activities (Carpenter et al 2011;Stanley et al 2012). The conversion of natural landscapes for human use has thus been shown to alter the sources, composition and reactivity of fluvial OM with significant effects on carbon cycling in freshwaters (Parr et al 2015;Petrone et al 2011;Rosemond et al 2015;Wilson and Xenopoulos 2009). Our ability to predict future changes in fluvial OM and associated ecological consequences in response to increasing anthropogenic pressures is however hampered by our limited understanding of the processes involved as well as by the fact that DOM and POM fractions are often investigated separately rather than simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…algae, macroinvertebrates, fishes) and food web compartments (e.g. "green" pathways involving primary producers, "brown" pathways involving heterotrophic bacteria and fungi [11,12]); and many interacting environmental factors are also involved, such as land use, flooding, and stream size, affect stressor-response relationships [13][14][15]. Temporal factors also complicate relationships, with legacy (historic) nutrient sources contributing to stressors [3,16,17].…”
Section: Open Accessmentioning
confidence: 99%